Engaging athletes as research participants. A document analysis of published sport science literature - Mitchell, L.; Ratcliff, J.; Burke, L. M.; Forsyth, A. (European Journal of Sport Science, 2024)
Sport science practitioners utilise findings from peer reviewed research to inform practice. Fewer studies are conducted with high performance athletes, however, than those involving recreationally active participants. Noting that research findings from recreational athletes may not be generalisable to the elite, there is a need to engage the latter cohort in research with better potential to influence health and performance. This study identified methods used to engage and recruit highly trained, elite and world class athletes as research participants. A document analysis was conducted using a purposive sample of peer-reviewed sport science literature. All articles published in 2022 from 18 highly ranked sport science journals were screened for inclusion. Studies investigating athletes ranked as highly trained/national level or above were included. All details related to participant recruitment were extracted from included articles, with the content being coded and thematically analysed using an interpretivist approach. A total of 439 studies from the 2356 screened were included in the analysis. Five primary themes of recruitment strategies were identified, beneath an overarching strategy of purposeful, convenience sampling. Recruitment themes related to the use of a gatekeeper, the research environment providing convenient access to athletes, promoting the study electronically, utilising professional networks and recruiting at training or competition. Engaging athletes through a gatekeeper is a prominent strategy to involve elite athletes in research. It is suggested that researchers work collaboratively with team or organisation personnel to promote recruitment, creating co-designed approaches that address issues most relevant to athletes and staff.